Answer:
A = (2p + 9) (2p - 9)
B = (x - 9) (x - 4)
Step-by-step explanation:
For A : Rewrite 4p^2 as (2p)^2.
(2p)^2−81
Rewrite 81 as 9^2.
(2p)^2−9^2
Since both terms are perfect squares, factor using the difference of squares formula, a^2 − b^2 = ( a + b ) ( a − b ) where a = 2p and b = 9 .
(2p + 9) (2p − 9)
For B : Consider the form x^2 + bx + c . Find a pair of integers whose product is c and whose sum is b . In this case, whose product is 36 and whose sum is − 13 .
-9, -4
(x - 9) (x - 4)
I hope this helps.
Answer:5*11
Step-by-step explanation:
Answer: (6 , 3)
Step-by-step explanation: Given
x + 3y =15 ------- equation 1
4x + 2y = 30 --------- equation 2
x = 15 - 3y
Put value of x in equation 2
4 (15 - 3y) + 2y = 30
60 - 12y + 2y = 30
-10y = -30
divide by '-10' on both sides
y = 3
now, put value of y in equation 1
x + 3(3) = 15
x + 9 = 15
x = 15 - 9
x = 6
So , (x , y) = (6 , 3)
Answer:
Decrease in dollars is $555.00, $6845.00 was in his account at the end of last year.
Step-by-step explanation:
7400 times 7.5/100
=74 times 7.5
=$555.00
7400-555=$6845.00